Analysis of the diffraction efficiency in transverse configuration in sillenite crystals Bi12TiO20 - Villamizar Amado, Astrid Lorena (2018)
A theoretical study on sillenite crystal where it obtained an analytics expression for diffraction efficiency in the on-Bragg regime in transverse configuration (K ⊥< 001 >) is realized. It is considered non-mobile transmission gratings. An analysis of diffraction efficiency considering the non-uniformity of gratings, material properties, external parameters the applied field or the intensity of beam input or polarization or the optical activity of the crystal beetwen others is realized.